2000
DOI: 10.1046/j.1440-1622.2000.01903.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Heller Myotomy For Achalasia

Abstract: Laparoscopic Heller myotomy is a technically challenging procedure that provides good early palliation of the symptoms associated with achalasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 29 publications
(45 reference statements)
0
2
0
2
Order By: Relevance
“…In our study, neither the institutional nor the individual surgeon's operative experience influenced the intraoperative complication rate, dysphagia scores, the risk of reoperation, or overall patient satisfaction. Other studies, however, have shown an improvement in the complication rate and postoperative symptoms after performing more cardiomyotomies [11][12][13]. This might be explained by the fact that laparoscopic cardiomyotomy was commenced nearly 12 months after we commenced laparoscopic fundoplication, and surgeons were already familiar with laparoscopic approaches to the distal esophagus.…”
Section: Discussionmentioning
confidence: 98%
“…In our study, neither the institutional nor the individual surgeon's operative experience influenced the intraoperative complication rate, dysphagia scores, the risk of reoperation, or overall patient satisfaction. Other studies, however, have shown an improvement in the complication rate and postoperative symptoms after performing more cardiomyotomies [11][12][13]. This might be explained by the fact that laparoscopic cardiomyotomy was commenced nearly 12 months after we commenced laparoscopic fundoplication, and surgeons were already familiar with laparoscopic approaches to the distal esophagus.…”
Section: Discussionmentioning
confidence: 98%
“…Zunehmend wird für die Myotomie der laparoskopische Zugangsweg gewählt und als Refluxprophylaxe eine anteriore Semifundoplicatio durchgeführt [2,4,11,12,19,23,31]. Bei deutlich längerer Operationsdauer sind Morbidität und Mortalität gleichfalls gering [2,4,11,12,19,23,26,30,31].…”
Section: Schlüsselwörterunclassified
“…Bei deutlich längerer Operationsdauer sind Morbidität und Mortalität gleichfalls gering [2,4,11,12,19,23,26,30,31]. Die Patienten erreichen die normale Aktivität früher als nach Laparotomie, und das kosmetische Ergebnis ist günstiger, was vor allem für jüngere Patienten von Bedeutung ist.…”
Section: Schlüsselwörterunclassified
“…To prevent GER, a loose fundoplication is often performed (270-degree wrap or Toupet procedure). Surgical myotomy results in excellent symptom relief, with mortality rates similar to those with balloon dilation [27,28]. Using the laparoscopic method for the myotomy shortens the hospital stay considerably (when compared with the open surgical method), and patients are often back to work within 2 to 4 weeks.…”
Section: Therapymentioning
confidence: 99%